Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.analchem.0c05275
|View full text |Cite
|
Sign up to set email alerts
|

Signal-Amplified Detection of the Tumor Biomarker FEN1 Based on Cleavage-Induced Ligation of a Dumbbell DNA Probe and Rolling Circle Amplification

Abstract: Flap endonuclease 1 (FEN1), an endogenous nuclease with the ability to cleave the 5′ overhang of branched dsDNA, is of significance in DNA replication and repair. The overexpression of FEN1 is common in cancer because of the ubiquitous upregulation of DNA replication; thus, FEN1 has been recognized as a potential biomarker in oncological investigations. However, few analytical methods targeting FEN1 with high sensitivity and simplicity have been developed. This work developed a signal-amplified detection of FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Previous studies have indicated that FEN1 was overexpressed in multiple solid tumors like lung cancer and breast cancer with aggressive clinical implications 11 , 12 . In addition to its significance, in situ sensing of oncogenic FEN1 with DNA nanosphere or dumbbell DNA probe has been developed for early diagnosis and precision medicine 23 , 24 . Actually, a recent study noted that FEN1 expression was elevated in HCC tissues by analyzing bioinformatic data 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that FEN1 was overexpressed in multiple solid tumors like lung cancer and breast cancer with aggressive clinical implications 11 , 12 . In addition to its significance, in situ sensing of oncogenic FEN1 with DNA nanosphere or dumbbell DNA probe has been developed for early diagnosis and precision medicine 23 , 24 . Actually, a recent study noted that FEN1 expression was elevated in HCC tissues by analyzing bioinformatic data 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, nucleic acid detection technology has been a research hotspot for investigators, because identifying cancer markers is very signicant for cancer diagnosis and prognosis. [1][2][3] Gene mutations and abnormal gene expression are early molecular manifestations of some cancers. 4 At the same time, studies have shown that gene mutations play an important role in 5-10% of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional assays, including western blot, reverse transcription-polymerase chain reaction (RT-PCR), and enzyme-linked immunosorbent assay (ELISA) [ 1 , 3 , 4 ] had already been utilized to detect FEN1. Several novel strategies were also designed for FEN1 detection [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. For instance, Zhang et al [ 9 ] proposed a DNA-based fluorescent biosensor to evaluate FEN1 activity in living cells.…”
Section: Introductionmentioning
confidence: 99%